E-TRUST AND E-SERVICE QUALITY INFLUENCE ON E-LOYALTY USERS OF BNI E-BANKING IN SUBANG DISTRICT - Muhammad Fajar; Gugyh Susandy; Devy Widya Apriandi (STIESA Press, 2019)
The technology is not separated of daily life, both at work, school or for the mere entertainment we use technology. The technology is evolving fast, one of the interesting phenomenon is the emergence of the Internet technology. The development of information technology, telecommunications, and the internet causing the manufacturer provides business applications that use the internet network, one of the applications is e-banking. The purpose of this research is to know the influence of e-Trust and e-Service Quality on e-Loyalty, e-Banking user BNI in the Regency of Subang. The research method used was explanatory survey methods. The data used is data interval. Statistical methods for testing data using SPSS SPPS 20 for windows. From the results of the research noted that the e-Trust influential significantly to e-Loyalty and e-Service Quality effect significantly to e-Loyalty. As well as e-Trust and e-Service Quality simultaneously significant effect against the e-Loyalty.